SUSTAINABILITY REPORTING FOR CSR DISCLOSURES: A CASE STUDY IN OIL AND GAS INDUSTRY - Sihotang, Parulian; Effendi, Subagio (Badan kebijakan Fiskal, 2009)
Sustainability Reporting has been used quite extensively in communicating company accountability towards its broad-based stakeholders. The report, widely known as the triple bottom line (TBL) report, discloses three performance indicators of any company: economic, social and environmental performance. Social and environmental performance are usually understood as Corporate Social Responsibility (CSR). This article will investigate how Sustainability Reporting principles developed by the Global Reporting Initiatives (GRI) have been implemented by the oil and gas industry in order to stimulate and enhance CSR practices and disclosures. GRI-based sustainability reporting is currently the most recognized reporting principles implemented by various industries worldwide. Content analysis on selected Sustainability Reporting of selected international oil companies will be conducted to identify the extent to which their CSR practices and disclosures have been in line with GRI principles. Furthermore, this research will explore whether CSR reporting applied by international oil multinationals could be implemented in developing countries such as Indonesia. Finally, it is expected that this exploratory research will be able to introduce and develop the Indonesian principles on CSR disclosures using GRI-based Sustainability Reporting published by the oil and gas companies operating in Indonesia.